Techno-economic analysis of a liquid air energy storage system combined with calcium carbide production and waste heat recovery. (April 2023) - Liu, Qingshan; Arabkoohsar, Ahmad; Liu, Yingwen; He, Zhilong
Abstract: Liquid air energy storage is one of the most promising solutions for the large penetration of renewable energy, but its potential in future industrial scenarios should be explored more. In this regard, a novel energy storage system combined with a calcium carbide production process, a steam Rankine cycle, an organic Rankine cycle, and a hot water unit is proposed in the current study. The thermodynamic and economic performances of the reference system are investigated, and the impacts of the critical parameters on the system performance are reported. The results show that the proposed system has round-trip energy and exergy efficiencies of 45.3 % and 49.0 %, which are 3.1 % and 11.5 % higher than those of stand-alone energy storage systems in the same category of technology. The economic analysis presents attractive and promising results, including a payback period of 1.35 years (which is of course based on special considerations related to the specific case study of the project in China), a total profit of 168.8 million USD, and a levelized cost of storage of 382–888 USD/MWh during the life period of the proposed system. Meanwhile, the calcium carbide production process can save electricity costs by 4.6 % owing to the system integration. The implementation of the proposed system will be of great practical significance for advancing the functionality of energy storage systems, specifically liquid air energy storage units, in industrial processes. Highlights: A novel energy storage system with CaC2 process and waste heat recovery is proposed. The round-trip energy and exergy efficiencies of the system are 45.3 % and 49.0 %. A payback period of 1.35 years and a total profit of 168.8 million USD are obtained. The levelized cost of storage ranges from 382 USD/MWh to 888 USD/MWh. CaC2 production process saves electricity costs by 4.6 % owing to system integration.